Numerical Investigation on Heat Transfer Characteristics and Pressure drop of a Triangular Slotted Pin Fin Heat Sink - P.Bhaskara Rao*, B.Srikanth, G.Ramprasad (International Journal of Advanced Science and Technology, 2020)
The present work focus on the numerical investigates the heat transfer and pressure drop of uni triangular slotted finned heat sinks (USFHS) and bi triangular slotted finned heat sinks (BSFHS) instant of solid finned heat sinks (SFHS) with various Reynolds number and constant heat flux applied at a bottom rectangular plate of heat sinks. Overall heat sinks are made of Aluminum material and air is working medium in this investigation. The numerical results are shown. The temperature profile of the heat sinks is less in USFHS and BSFHS compared with SFHS at the constant heat flux. Further, the Nusselt number, at all Reynolds numbers, of a triangular slotted heat sink is more than that of solid pin fin heat sink. The pressure drops are less in USFHS and BSFHS model in comparison to that of SFHS model with the inline arrangement. The system performance parameter is 57.9% and 63.18% higher with a USFHS and BSFHS arrangement in place of SFHS arrangement. The present work focus on the numerical investigates the heat transfer and pressure drop of uni triangular slotted finned heat sinks (USFHS) and bi triangular slotted finned heat sinks (BSFHS) instant of solid finned heat sinks (SFHS) with various Reynolds number and constant heat flux applied at a bottom rectangular plate of heat sinks. Overall heat sinks are made of Aluminum material and air is working medium in this investigation. The numerical results are shown. The temperature profile of the heat sinks is less in USFHS and BSFHS compared with SFHS at the constant heat flux. Further, the Nusselt number, at all Reynolds numbers, of a triangular slotted heat sink is more than that of solid pin fin heat sink. The pressure drops are less in USFHS and BSFHS model in comparison to that of SFHS model with the inline arrangement. The system performance parameter is 57.9% and 63.18% higher with a USFHS and BSFHS arrangement in place of SFHS arrangement.